Frontal Balloon Sinuplasty in Complicated Acute Pediatric Rhinosinusitis (ARS) - Smrithi Chidambaram; Benjamin M. Wahle; David S. Leonard (Case Reports in Otolaryngology)
Utilization of frontal balloon sinuplasty in pediatric complicated acute rhinosinusitis (ARS) is demonstrated to be a safe and expedient alternative to other procedures such as trephination or functional endoscopic sinus surgery (FESS) in this case series. We performed a retrospective review of six pediatric cases of frontal balloon sinuplasty for ARS with intracranial complications at a tertiary academic center. Patients underwent unilateral (n = 5) or bilateral dilation (n = 1) in addition to functional endoscopic sinus surgery (FESS) including anterior ethmoidectomy (n = 5) and maxillary antrostomy (n = 6). This technique effectively addressed frontal sinus obstruction and served as an alternative to procedures such as trephination or functional endoscopic sinus surgery. No immediate or short-term complications of balloon dilation were observed in these cases. A larger cohort and extended follow-up are necessary to determine the use and long-term impact of this technique.